Impact of New Digital Media on Conventional Media and Visual Communication in Jordan - Mohammad Alzubi, Ahmad (Journal of Engineering, Technology, and Applied Science (JETAS), 2022)
The purpose of the present research was to assess the impact of new digital media on conventional media and visual communication has been significant. Digital media has transformed how information is created, distributed, and consumed, and has profoundly affected traditional forms of media such as print newspapers, magazines, and television. One of the main ways that new digital media has affected traditional media is through the emergence of online platforms and social media. These platforms have allowed individuals and organizations to publish and share content with a global audience, often bypassing traditional gatekeepers such as editors and broadcasters. This has led to the democratization of media, as anyone with an internet connection can now potentially reach a large audience. Digital media has also led to the rise of new forms of visual communication, such as digital graphics, video, and animation. These forms of media allow for more interactive and immersive experiences and have become increasingly popular with audiences. In addition, digital media has also had an impact on the business models of traditional media organizations. Many have struggled to adapt to the shift towards digital advertising and subscriptions, leading to a decline in revenues and layoffs in some cases. It may be the case that the impact of new digital media on conventional media and visual communication has been significant and wide-reaching and will likely continue to shape the media landscape for years to come.